Development of Ecet-Ecetan Motifs in the Legong Nolin Repertoire | Pengembangan Motif Ecet-Ecetan Pada Repertoar Legong Nolin - I Putu Yoga Nandana (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
This article describes the process of creating Legong Nolin to implement the Freedom to Learn Free Campus program in Thematic Real Work Lectures conducted in Pujungan Village, Pupuan District, Tabanan Regency. Pujungan Village has Nolin art based on local wisdom, but this art has been in a vacuum for the last few years, and there is no generation to continue this art. With this KKNT, the authors intend to develop Nolin's gamelan repertoire so that this art is increasingly in demand by the community so that Nolin becomes an artistic identity for Pujungan Village. The author uses three methods in making this article, including the exploration method, the improvisation method, and the forming method. Nolin art in Pujungan Village must get attention so that it does not become a vacuum like before. Therefore, it is essential to create a new generation of musicians so that they can participate in preserving Nolin's art. The benefits of this activity are that Nolin's gamelan repertoire is maintained to continue to exist in society and that Nolin's art has future generations.